PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPRATIVE LEARNING TIPE JIGSAW PADA MATA PELAJARAN IPA KELAS IV SD NEGERI POJA II KABUPATEN SUMENEP - MOH. FADLI & SIFUL ARIFIN (Institut Kariman Wirayudha Sumenep, 2022)
Abstract The main objective of this study was to determine how the Jigsaw Cooperative Learning strategy affects the scientific learning outcomes of fourth-grade students of Poja II Elementary School, Sumenep Regency. Quantitative methods and pre-experimental designs, more specifically, quasi-experimental designs were used in this study. There were twelve fourth-grade students of Poja II Elementary School, Sumenep Regency who were used as research subjects. Information on students' learning outcomes in class was included in the data on learning achievement. Assessment of learning outcomes and observation sheets were used for data collection, and T-tests and descriptive statistical methods were used for data analysis. The findings of the study showed that students' science learning outcomes increased rapidly when the Jigsaw Cooperative Learning model was used. The initial pretest average score was 59 and then increased to 83 in the posttest. The Jigsaw learning model can affect science learning outcomes, based on the findings of the study. In addition to encouraging student participation, the jigsaw learning model makes learning fun and interesting, making it easier for students to understand the subject. The results of the study showed that the science learning outcomes of fourth-grade students of Poja II Elementary School, Sumenep Regency were positively affected by the application of the Jigsaw learning model